Analisis Kepatuhan Wajib Pajak Kendaraan Bermotor: Pengaruh Tarif Progresif dan Sanksi Pajak di Samsat Gowa - Trie Akra Putri; Muhammad Nasrun; Masrullah (Jurnal Ekonomi Islam, 2026)
This study aims to analyze the effect of progressive tax rates and tax sanctions on motor vehicle taxpayer compliance at the Gowa Regional Samsat Office. This study employs a quantitative approach utilizing primary data obtained through questionnaires distributed to motor vehicle taxpayers. The sampling technique used is incidental sampling with a total of 100 respondents. The data analysis method applied is multiple linear regression analysis aided by the SPSS program. The results of the study indicate that progressive tax rates have a positive and significant effect on motor vehicle taxpayer compliance. Tax sanctions also have a positive and significant effect on motor vehicle taxpayer compliance. These findings indicate that the application of fair tax rates and the strict enforcement of sanctions can improve taxpayer discipline in fulfilling their tax obligations. This study is expected to serve as evaluation material for local governments in enhancing the effectiveness of Motor Vehicle Tax revenue in Gowa Regency.